Stem Cell-Based Therapy for Asherman Syndrome: Promises and Challenges. (8th June 2021) - Gao, Yiyin; Wu, Guijie; Xu, Ying; Zhao, Donghai; Zheng, Lianwen
Asherman syndrome (AS) has an adverse effect on reproductive health and fertility by affecting endometrial regeneration. Stem cell-based therapies hold promise for future use in activating non-functional endometrium and reconstructing the endometrium in vivo. It has been postulated that various endometrial stem cells (EnSCs) are responsible for endometrial regeneration. Numerous studies have focused on bone marrow-derived stem cells (BMDSCs), which may provide new ideas for repairing endometrial lesions and reconstructing the endometrium. Other sources of stem cells, such as menstrual blood, umbilical cord, and amniotic membrane, have also attracted much attention as candidates for transplantation in AS. This review discusses the features and specific biomarkers among four types of resident endometrial stem cells, applications of four different sources of exogenous stem cells in AS, and development of stem cell therapy using biomaterials and exosomes.